STUDY OF STRENGTH OF FUMERAL BONE OF RATS AFTER FILLING BONE TISSUE DEFECTS WITH BONE CEMENT BASED ON TRICALCIUM PHOSPHATE - Filipenko, V.A.; Poplavska, K.S.; Karpinskaya, O.D.; Karpinsky, M.Yu. (World of Medicine and Biology, 2022)
There are bone defects that do not heal on their own, despite the ability of bone tissue to fully regenerate. These defects occur due to degenerative-dystrophic diseases, injuries, resections of tumors and tumor-like formations, metastatic lesions, as a result of the development of aseptic instability after primary arthroplasty. Autogenous material for transplantation is the most acceptable, but its use depends on the quality of the bone. Allografts have compensated for the shortcomings of autografts, but the risk of infection and ethical issues limit the use of this material. The group II cement that we offer retains the properties of tricalcium phosphate-based materials: high biocompatibility, osteoconductive and osteointegrative qualities, and, due to strengthening by HA whiskers, it has higher strength and slower biodegradation time.
Keywords: bioceramics; α-tricalcium phosphate; calcium phosphate cement; orthopedic surgery; bone regeneration